Quality control of Ganoderma lucidum by using C, H, O, and N stable isotopes and C and N contents for geographical traceability - Zhang, Ying; Jiang, Kunxia; Chen, Sisi; Wang, Lina; Zhang, Xun; Xu, Wen; Yam, Mun Fei; Wu, Changhui; Xu, Wei; Lin, Yu (Frontiers in Plant Science, 2023)
Rationale Ganoderma lucidum (G. lucidum) is a popular medicinal fungus that has been used in traditional medicine for decades, with its provenance influencing its medicinal and commercial worth. The amount of active ingredients and the price of G. lucidum from different origins vary significantly; hence, fraudulent labeling is common. Reliable techniques for G. lucidum geographic verification are urgently required to safeguard the interests of consumers, producers, and honest dealers. A stable isotope is widely acknowledged as a useful traceability technique and could be developed to confirm the geographical origin of G. lucidum. Methods G. lucidum samples from various sources and in varying stages were identified by using δ13C, δD, δ18O, δ15N, C, and N contents combined with chemometric tools. Chemometric approaches, including PCA, OPLS-DA, PLS, and FLDA models, were applied to the obtained data. The established models were used to trace the origin of G. lucidum from various sources or track various stages of G. lucidum. Results In the stage model, the δ13C, δD, δ18O, δ15N, C, and N contents were considered meaningful variables to identify various stages of G. lucidum (bud development, growth, and maturing) using PCA and OPLS-DA and the findings were validated by the PLS model rather than by only four variables (δ13C, δD, δ18O, and δ15N). In the origin model, only four variables, namely δ13C, δD, δ18O, and δ15N, were used. PCA divided G. lucidum samples into four clusters: A (Zhejiang), B (Anhui), C (Jilin), and D (Fujian). The OPLS-DA model could be used to classify the origin of G. lucidum. The model was validated by other test samples (Pseudostellaria heterophylla), and the external test (G. lucidum) by PLS and FLDA models demonstrated external verification accuracy of up to 100%. Conclusion C, H, O, and N stable isotopes and C and N contents combined with chemometric techniques demonstrated considerable potential in the geographic authentication of G. lucidum, providing a promising method to identify stages of G. lucidum.